2014
DOI: 10.2478/bvip-2014-0055
|View full text |Cite
|
Sign up to set email alerts
|

Flow Cytometric Determination of the Expression of gp 51 Protein of Bovine Leukaemia Virus in Experimentally Infected Sheep

Abstract: The study was performed on lambs experimentally infected with bovine leukaemia virus (BLV). The presence of BLV antibodies in sera of infected animals was detected by agar gel immunodiffusion test and ELISA. Proviral DNA was detected by PCR and nested PCR. Dual-colour flow cytometry analysis was performed with the use of specific monoclonal antibodies against lymphocyte CD markers and gp51 viral envelope protein, followed by incubation with fluorescent-labelled secondary antibodies conjugated with FITC or PE. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Mammary gland immunity is largely dependent upon neutrophilic functions. Many studies have investigated the effects of BLV infection on lymphocyte subsets in infected animals (9,29,30), B cell vitality (11,28,31) and neutrophil functions (10,28). Bovine leukaemia virus can be the reason for changes in milk production and fertility in cows.…”
Section: Discussionmentioning
confidence: 99%
“…Mammary gland immunity is largely dependent upon neutrophilic functions. Many studies have investigated the effects of BLV infection on lymphocyte subsets in infected animals (9,29,30), B cell vitality (11,28,31) and neutrophil functions (10,28). Bovine leukaemia virus can be the reason for changes in milk production and fertility in cows.…”
Section: Discussionmentioning
confidence: 99%
“…Tetraploid DI was determined in control cell line 1301. In our earlier investigations (Szczotka et al 2007) numerous sister chromatid exchanges (SCEs) in metaphasal chromosomes of BLV-infected lymphocytes were found. The obtained results indicated that BLV may cause chromosomal disorders (mutagenesis) in blood lymphocytes of leukaemic cattle.…”
Section: Discussionmentioning
confidence: 89%